Development of E-Books as Educational Media to Introduce Disasters to Early Childhood - Heni Nafiqoh; Ratna Dwi Nurcahyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia's geographical position along the Pacific Ring of Fire makes it highly vulnerable to natural disasters such as earthquakes, floods, and tsunamis. Early childhood education plays a critical role in preparing young learners to recognize hazards and respond appropriately during emergencies. However, disaster education for children is often limited to conventional methods that lack interactivity and developmental alignment. This study aimed to develop and evaluate an interactive e-book designed to enhance disaster preparedness among children aged 4–6 through a developmentally appropriate, engaging, and multimedia-based approach. Using an Educational Design Research (EDR) framework, the study involved iterative phases of needs analysis, product design, expert validation, revision, and limited field testing. Data were collected through interviews, observation sheets, teacher questionnaires, and expert validation rubrics. The e-book incorporated child-friendly illustrations, animations, narration, and interactive games. Expert validators rated the e-book as "Very Eligible" (97.9%) based on content accuracy, visual appeal, language clarity, and interactivity. A field test with 12 children at PAUD Al Hidayah showed a significant improvement in disaster knowledge, with posttest scores increasing from an average of 35.83 to 72.5. Children demonstrated high engagement and adaptability when interacting with the e-book, reinforcing the effectiveness of multimedia tools in early disaster education. The findings support integrating digital media into early childhood curricula to foster resilience and disaster literacy. Future research should explore the long-term behavioral impacts of disaster e-books and their integration with emerging digital platforms such as mobile apps and augmented reality to broaden access and educational impact.